Problematyka Powstania Wielkopolskiego 1918/1919 w wybranych dziedzinach kultury (w literaturze i twórczości plastycznej) - Karwat, Janusz (Studia Europaea Gnesnensia, 2015)
Apart from historical studies and monographs, cultural initiatives are an important way of commemorating the Greater Poland Uprising of 1918-1919. Among such undertakings, literary works and products of visual arts are predominant. The greatest number of those are created on round anniversaries of this armed effort. One of their prominent features is realism, as they are intended for the broadest audience.